1995
DOI: 10.1007/bf02208653
|View full text |Cite
|
Sign up to set email alerts
|

IgA anti-endomysial antibodies on human umbilical cord tissue for celiac disease screening

Abstract: Since celiac disease screening by traditional IgA anti-endomysial antibody test is limited by high costs of monkey esophagus commercial kits as well as by rising ethical problems related to the endangered species, the identification of an inexpensive and commonly available substrate for this antibody determination is urgently required. To achieve this goal, we compared the prevalence of IgA anti-endomysial antibodies detected on monkey esophagus with that on human umbilical cord. Fifty-seven (95%) of 60 untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 21 publications
3
70
0
8
Order By: Relevance
“…In 1995, VOLTA et al (71) , using human umbilical cord instead of monkey's esophagus as substrate, showed the same specificity and sensitivity of EmA IgA in both techniques. These data were then confirmed by BAGNASCO et al (6) in relatives of patients with CD.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In 1995, VOLTA et al (71) , using human umbilical cord instead of monkey's esophagus as substrate, showed the same specificity and sensitivity of EmA IgA in both techniques. These data were then confirmed by BAGNASCO et al (6) in relatives of patients with CD.…”
Section: Introductionmentioning
confidence: 95%
“…Monkey's esophagus is ethically questionable for large scale screening (71) . The endomysial antibody has been found to have a greater specificity and sensitivity (15,33) .…”
Section: Considerations About Emamentioning
confidence: 99%
“…All subjects were screened for IgA-EmA according to Volta and cols. (15), using indirect immunofluorescence with cryostatic sections of human umbilical cord as substrate, with initial dilution 1/2.5. Secondary anti-human IgA conjugate antibodies (GMK, Porto Alegre, Brazil) were used in the reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Positive samples were tittered up to the end point; positive and negative controls were used for each bath. This test was used due its high sensitivity (95%) and specificity (100%) for the diagnosis of CD (15).…”
Section: Methodsmentioning
confidence: 99%
“…EMA association with CD was first described in 1984 [49] and its detection rapidly became the serological test of choice, due to its specificity of almost 100%. The use of human umbilical cord as substrate has been proposed as a valid alternative to the monkey esophagus [50][51][52].…”
Section: Biological Markersmentioning
confidence: 99%